Structure and Diagenesis in Upper Carboniferous Tight Gas Reservoirs in NW Germany - Wüstefeld, Patrick (KIT Scientific Publishing, 2018)
Upper Carboniferous sandstones are important tight gas reservoirs in Central Europe. This field-based study, conducted in a km-scale reservoir outcrop analog (Piesberg quarry, Lower Saxony Basin, NW Germany), focused on the diagenetic control on spatial reservoir quality distribution. Geothermometers were used to characterize a fault-related thermal anomaly. A prototype workflow based on terrestrial laser scanning is presented, which allowed for the automated detection and analysis of fractures.